2022
DOI: 10.1111/jfpp.16433
|View full text |Cite
|
Sign up to set email alerts
|

The chemical composition analysis of dwarf saltwort ( Salicornia bigelovii Torr.) and its preservative effects on snakehead fish fillets

Abstract: In this study, the nutritional component and chemical constituents of Salicornia bigelovii Torr. were investigated, as well as their preservative effects on aquatic products. LC–MS of S. bigelovii extracts detected 34 compounds, eight flavonoids were identified based on standard substance. Camellianin A and noreugenin were identified for the first time in S. bigelovii. Furthermore, the S. bigelovii could reduce the fish fillet loss rate and inhibit the growth of microorganisms in aquatic products that impact c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Salicornia has shown high levels of vitamin C; the content of ascorbic and dehydroascorbic acids is more than 100 mg/100 g. S. bigelovii shows a high amount of β-carotene (15.9 mg/100 g of fresh weight (fw)), which is a good source of vitamin A [10,18]. Lima et al, 2020 have reported a high content of the soluble fat vitamin E, α-Tocopherol (241 µg/100 g fw), and vitamin B 2 and B 5 (with a relative content of 4.14% in 0.5 g) in S. ramosissima and S. bigelovi, respectively [19,20].…”
Section: Principal Phytochemicals (Especially Polyphenols) Identified...mentioning
confidence: 99%
“…Salicornia has shown high levels of vitamin C; the content of ascorbic and dehydroascorbic acids is more than 100 mg/100 g. S. bigelovii shows a high amount of β-carotene (15.9 mg/100 g of fresh weight (fw)), which is a good source of vitamin A [10,18]. Lima et al, 2020 have reported a high content of the soluble fat vitamin E, α-Tocopherol (241 µg/100 g fw), and vitamin B 2 and B 5 (with a relative content of 4.14% in 0.5 g) in S. ramosissima and S. bigelovi, respectively [19,20].…”
Section: Principal Phytochemicals (Especially Polyphenols) Identified...mentioning
confidence: 99%
“…Plant-derived antioxidants are extracted from natural plants such as Salicornia spp. with antioxidant properties, they can effectively inhibit or delay the oxidative decomposition and deterioration of food ingredients, thereby enhancing the stability of food and extending their storage period [ 118 ].…”
Section: Nutrition Profile and Health Impactsmentioning
confidence: 99%
“…Salicornia can be utilized as ‘functional foods’ since it contains metabolites with bioactivities [ 118 ]. For example, the S. brachiata plant possesses nutritional antioxidants, scavenging activities, amino acids, flavonoids, essential fatty acids and polyunsaturated fatty acids, making it a promising ideal plant that can used as a functional food or as a dietary supplement in nutraceutical industries [ 116 ].…”
Section: Nutrition Profile and Health Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has confirmed that S. bigelovii possesses a high content of flavonoids [ 7 ], alkaloids, chromones [ 8 ], and sterols [ 9 ], and Quercetin and Quercetin-3-O have also been isolated from S. bigelovii along with β-D-glucoside, Rutin, and Isorhamnol-3-O-β-flavonoids such as D-glucoside. Previous studies have determined that S. bigelovii contains multiple flavonoids, and camellianin A and noreugenin, which are previously unreported compounds, have been identified [ 10 ].…”
Section: Introductionmentioning
confidence: 99%